Penguatan Kemampuan Matematika Dasar Siswa Sma Melalui Kegiatan Matrikulasi - Jana, Padrul (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2018)
The aim of the matriculation is to improve the basic mathematics skills of high school students in order to ease the learning process in the next level. The method of this research is started with pretest, explaining material, exercise, postest and the last one in evaluation.The result of this activity is the increase of basic mathematics comprehension of the students which was 48,5% and the final result showed that student who passed the criterion of minimum mastery were 51,4%.